Thyroid screening in prediabetes: Does it have any role? - Thapa, S.; Gyawali, P.; Tamrakar, R.; Risal, P. (Journal of Diabetes and Endocrinology Association of Nepal, 2020)
Background: Thyroid dysfunction and hyperglycemia are common metabolic problem. Unrecognized thyroid dysfunction may amplify existing cardiovascular disease risk in hyperglycemic subjects. Early recognition and management of thyroid dysfunction helps to control blood glucose and prevent associated morbidity. The aim of this study was to assess thyroid function among prediabetics and compare it with healthy controls. Methods: This study conducted in Kathmandu University hospital was reviewed and approved by Institutional review committee. The total of 200 participants were recruited for the study among which 106 were prediabetics (HbA1c 5.7–6.4%) and 94 apparently healthy controls (HbA1c<5.7%). We excluded known cases of diabetes mellitus, thyroid disorder, pregnant and those on medications that interfere with thyroid function and/or glucose metabolism. Results: Among the total participants 57.5% (115) were female and 42.5 % (85) were male. Prediabetics had significantly higher TSH 3.0 (2.0, 4.9) in comparison to the control 2.61 (2.0, 3.9) population (p=0.004). Serum TSH was raised in 42 (21%) participants while 158 (79%) had normal thyroid function. The association between prediabetes and thyroid dysfunction was significant (p=0.04) with 26.4% of prediabetics having thyroid dysfunction compared to 14.9% in normal group. Thyroid dysfunction was independently associated with prediabetes (OR=2.38; 95% CI: 1.17–4.17). Conclusions: Thyroid dysfunction is common finding among those with prediabetes. The cause of thyroid abnormality should be ascertained and treated appropriately to reduce the progression to diabetes mellitus and related complications. Though not routinely practiced, screening of thyroid disorder in patients with hyperglycemia could be beneficial.